Predictors of length of stay, reoperation, and readmission following total laryngectomy. (21st December 2016) - Helman, Samuel N.; Brant, Jason A.; Moubayed, Sami P.; Newman, Jason G.; Cannady, Steven B.; Chai, Raymond L.
Abstract : Objectives/Hypothesis: To identify relevant patient and surgical risk factors associated with prolonged length of stay, return to the operating room, and readmission within 30 days following total laryngectomy using the American College of Surgeons National Quality Improvement Program (ACS‐NSQIP) Study Design: Retrospective database study. Patients undergoing total laryngectomy alone for laryngeal cancer were identified from the ACS‐NSQIP database from 2005 to 2014. Methods: Multivariate logistic regression was used to identify independent predictors for prolonged length of stay, readmissions, and unplanned reoperations within 30 days. Results: Among 871 patients meeting inclusion and exclusion criteria, the median length of stay was 8.0 days (range, 0–130 days). Totally dependent functional status ( P < .01; odds ratio [OR]: 32.62), Black or African American race ( P = .029; OR: 1.75), and operative time ( P < .0001; OR: 1.15) were associated with prolonged length of stay. The overall rate of return to the operating room within 30 days was 12.4%. Contaminated wound status ( P = .025; OR: 3.53), operative time ( P = .015; OR: 1.10), steroid use ( P < .01; OR: 2.92), and smoking ( P = .05; OR: 1.60) were significantly associated with return to the operating room. Unplanned readmission rate was 11.9%, and 47.37% of readmissions were due to wound infection/pharyngocutaneous fistula. Dirty/contaminated wound classification ( P = .05; OR: 22.5) was associated with readmission on multivariate analysis. Conclusions: This is the first population‐level analysis to be performed on length of stay, readmission, and reoperation for total laryngectomy. Assessing and identifying modifiable risk factors on quality metrics may reduce overall cost and the burden on limited hospital resources. Level of Evidence: 4. Laryngoscope, 127:1339–1344, 2017